2017
DOI: 10.1080/09537104.2017.1366973
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous HIT syndrome post-knee replacement surgery with delayed recovery of thrombocytopenia: a case report and literature review

Abstract: Recently published reports have established a heparin-induced thrombocytopenia (HIT)-mimicking thromboembolic disorder without proximate heparin exposure, called spontaneous HIT syndrome. Although the pathophysiology remains unclear, anti-platelet factor 4 (PF4)/heparin antibodies possibly triggered by exposure to knee cartilage glycosaminoglycans or other non-heparin polyanions found on bacterial surfaces and nucleic acids have been postulated. We present a 53-year-old female receiving antithrombotic prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 31 publications
3
62
0
2
Order By: Relevance
“…These highly pathogenic antibodies are able to bind and cross‐link PF4 molecules with (nonheparin) platelet‐associated polyanions (chondroitin sulfate, polyphosphates) or even in the absence of polyanion altogether. Table lists various presentations of HIT in which most (or all) patients have aHIT antibodies …”
Section: Autoimmune Hit (Ahit)mentioning
confidence: 99%
See 3 more Smart Citations
“…These highly pathogenic antibodies are able to bind and cross‐link PF4 molecules with (nonheparin) platelet‐associated polyanions (chondroitin sulfate, polyphosphates) or even in the absence of polyanion altogether. Table lists various presentations of HIT in which most (or all) patients have aHIT antibodies …”
Section: Autoimmune Hit (Ahit)mentioning
confidence: 99%
“…Platelet activation assays performed both in the presence and absence of heparin are important in supporting a diagnosis of aHIT: Strong platelet activation at 0 U/mL heparin, which is enhanced in the presence of pharmacological concentrations of heparin (0.1‐0.5 U/mL UFH)—either using neat or diluted serum/plasma—with inhibition at 100 U/mL heparin, is the serological picture . The major U.S. reference laboratories that perform the SRA do not perform the test in the absence of heparin, contributing to aHIT underrecognition.…”
Section: Autoimmune Hit (Ahit)mentioning
confidence: 99%
See 2 more Smart Citations
“…Presumably, PF4 is bound to immunogenic complexes through binding to polyanionic bacterial surfaces or to chondroitin -sulfate released during infections or orthopedic surgery 3) . It has been reported that some patients receiving arthroplasty had positive tests for anti -PF4/heparin antibodies 4) . This review will summarize current clinical and laboratory features of PF4/heparin immunogenicity induced by arthroplasty during rheumatic diseases.…”
Section: Introductionmentioning
confidence: 99%